2012
DOI: 10.1136/bmj.e2333
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a diabetes education and self management programme (DESMOND) for people with newly diagnosed type 2 diabetes mellitus: three year follow-up of a cluster randomised controlled trial in primary care

Abstract: Objective To measure whether the benefits of a single education and self management structured programme for people with newly diagnosed type 2 diabetes mellitus are sustained at three years.Design Three year follow-up of a multicentre cluster randomised controlled trial in primary care, with randomisation at practice level.Setting 207 general practices in 13 primary care sites in the United Kingdom.Participants 731 of the 824 participants included in the original trial were eligible for follow-up. Biomedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
276
4
20

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(311 citation statements)
references
References 33 publications
11
276
4
20
Order By: Relevance
“…Inadequate glycemic control achieved 1 year after SDEP additionally supports the recommendations from the National Diabetes Guidelines to repeat the education and testing of diabetes knowledge at least annually [7]. The level of metabolic improvement 1 year after SDEP, as well as the positive effects of SDEP on diabetes knowledge, is in accordance with results from other studies [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 80%
“…Inadequate glycemic control achieved 1 year after SDEP additionally supports the recommendations from the National Diabetes Guidelines to repeat the education and testing of diabetes knowledge at least annually [7]. The level of metabolic improvement 1 year after SDEP, as well as the positive effects of SDEP on diabetes knowledge, is in accordance with results from other studies [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 80%
“…1 and Table 2). [30][31][32][33][34][35] We summarize the key study characteristics for these studies [30][31][32][33][34][35] in Appendix Table 5. No study evaluated mortality as a primary outcome.…”
Section: Long-term Clinical Outcomesmentioning
confidence: 99%
“…The United Kingdom's (UK) landmark multicentre trial of 824 participants randomised to Diabetes Education for Ongoing and Newly Diagnosed (DESMOND), a one day group course compared to attention control demonstrated improvements in weight, lipids and psychological variables but not glycaemic control 12 months later [3], although the benefits had reduced by 3 years [4]. This is in contrast to a recent systematic review and meta-analysis of 21 randomised controlled trials (RCT) (total n=2833) of group based DSME which concluded that HbA1c was significantly reduced by an average of 5mmol/mol at 6 and 12 months compared with the control group [5].…”
Section: Introductionmentioning
confidence: 99%